1976
DOI: 10.1111/j.1365-2494.1976.tb01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of herbage consumption by grazing cattle using measurements of eating behaviour

Abstract: numbers of animals required to detect true differences in intake at various levels of precision are presented.It is concluded that herbage consumption by grazing ariimals can be obtained from measurements of eating behaviour. AbstractFeed consumption (/). of a group of eight nonlactating Jersey cows strip-grazing oats at three stages of growth was estimated from number of eating bites (AQ and bite size (5) measurements using the expression, I = NxS. N was measured with four non-fistulated animals while S was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 9 publications
(17 reference statements)
2
19
0
2
Order By: Relevance
“…Intake of herbage was estimated from the mean number of eating bites recorded by the nonfistulated cows in 24 h and the mean bite size calculated for the fistulated cows (Chacon, Stobbs & Sandland, 1976). RESULTS…”
Section: Grazing Behaviour and Estimated Intake Of Herbagementioning
confidence: 99%
“…Intake of herbage was estimated from the mean number of eating bites recorded by the nonfistulated cows in 24 h and the mean bite size calculated for the fistulated cows (Chacon, Stobbs & Sandland, 1976). RESULTS…”
Section: Grazing Behaviour and Estimated Intake Of Herbagementioning
confidence: 99%
“…The form, maturity and availability of herbage have all been shown to affect voluntary intake (Stobbs 1974;Chacon et al 1976;Dougherty et al 1989a). Dougherty et al (1989b) showed that cattle consumed fresh leafy herbage at a greater rate than wilted or stemmy herbage.…”
Section: Herbage Intakementioning
confidence: 99%
“…In cows and sheep, the relation between the biting rate and height of sward or biting rate and bite size (herbage intake per bite) have been reported 3,5,8,15) Although these relations in horses have been mentioned2), few detailed studies have been published.…”
Section: Resultsmentioning
confidence: 99%